Addressing the Drought Induced Yield Variability in Karnataka Using Dry Spell Index (DSI) - Thimmegowda, M. N.; Manjunatha, M. H.; Pooja, R. S.; Huggi, Lingaraj; Jayaramaiah, R.; Sowmya, D. V.; Satish, G. S.; Nagesha, .L.; Arpitha, V. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during December, 2023 at the AICRP on Agrometeorology, University of Agricultural Sciences, GKVK, Bengaluru, Karnataka, India to study Dry spell and drought conditions for different districts of Karnataka. In this study, Dry Spell Index (DSI) was used to analyse annual and seasonal dry spells at 7- and 10-days’ time scale and its impact on crop productivity across different districts of Karnataka using long term rainfall data (1980-2020). The analysis of spatio-temporal distribution of average DSI-7 for annual rainfall during the period 1980–2020 in Karnataka revealed that a greater number of years falls under <4 average DSI with the range of 17 (Raichur)–40 years (Chamarajanagar, Mysore). During kharif and rabi season, most of the districts experienced more than 84 consecutive dry days for a season, indicated critical water stress that adversely affect crop performance. The impact of dry spells was found to be significant on crops such as sugarcane, ground nut, bajra and maize. Sugarcane, in particular, showed a negative correlation with DSI due to its long growth cycle and high-water demand. In contrast, drought-tolerant crops like pulses exhibited a significant positive correlation with DSI, highlighting their resilience and suitability for dryland farming. The study emphasizes the importance of selecting drought-resilient crops and adopting region-specific water management strategies to mitigate the risk of crop failure. These insights are crucial for promoting sustainable agricultural production and enhancing resilience against climatic variability in Karnataka’s dry zones.